Guía para la produccion de huevos y venta en Ferias - Rivera, Luciano Rodrigo; Dacal Arriaga, Mariana Andrea; Urraza, Maria Soledad; Gallardo, Alejandra Beatriz (EEA Valle Inferior, INTA, 2025)
EEA Valle Inferior, Agencia de Extensi{on Rural Conesa (AER Conesa)